Tryptophan enforced alg-iron oxide nanoconjugates: A potential evalution for synergistic cancer therapy - Benjamin, Amy Sarah; Nayak, Sunita (Biochimica et biophysica acta. General subjects, 2025)
The contribution of magnetic nanoparticles towards the diagnosis and therapy of cancer has seen an upward graph for the past decade owing to their excellent superparamagnetic properties and contrast imaging. The surface functionalization of these iron oxide nanoparticles plays a pivotal role in the toxicity, circulation, and agglomeration parameters of clinical translation. Natural-source-based sodium alginate is a very profound biomaterial used in all areas of tissue engineering. This paper aims to study the properties of alginate-coated iron oxide nanoparticles conjugated to the aromatic amino acid tryptophan for cancer targeting. The investigation involves fabrication of the conjugated nano-system followed by analysis of the physico-chemical properties using XRD and FT-IR, evaluation of its magnetic property using VSM which shows a good superparamagnetic behaviour, along with an excellent thermal stability as shown by TGA analysis. The hyperthermia activity of these particles shows a very good specific absorption rate followed by the antioxidant property of the nano-conjugate, which shows potential scavenging activity. The biocompatibility of these nanoparticles was studied on NIH-3T3 cell lines, which showed no toxic effects, thus making the nano-conjugate an efficient cancer-targeting and therapeutic agent for future cancer nanomedicine. [Display omitted] •Aromatic amino acids (AAA) are prominent cancer biomarkers which are studied for active targeting of cancer cells.•Tryptophan conjugated alginate/iron oxide nanoparticles (Trp-Alg IONPs) could be a potential targeting agent and provide synergistic activity for cancer nanomedicine.•Trp-Alg-IONPS conjugation and physico-chemical characterization showed excellent physical and morphological properties.•Excellent biocompatibility and reduced cytotoxicity results followed by reactive oxygen species (ROS) scavenging activity.•Hyperthermic activity of Trp-Alg-IONPS under external magnetic field leads to synergistic effect of iron oxide nanoparticles.